Special Circumstances and Populations. Issue 3 (July 2017) - Singh, Ashley; Foster, Megan; Chapman, Pamela; Hattab, Yousef; Alhassan, Sulaiman; Bajwa, Omar
Abstract : Venous thromboembolism is a condition that includes both deep venous thrombosis and pulmonary embolism. Venous thromboembolism disease can result because of a combination of risk factors, including patient-related, treatment-related, and, more specifically, cancer-related factors. It is not disease-specific or a population-specific disorder, but it is more prevalent in certain specialty populations. This article will cover those specialty populations including cancer, pregnancy, and athletes.